SECONDARY OCULAR HYPERTENSION AND GLAUCOMA FOLLOWING INTRAVITREAL TRIAMCINOLONE ACETONIDE INJECTION - Касимов Е. М.; Агаева Ф. А.; Керімов М. І. (World of Medicine and Biology, 2014)
A retrospective analysis of 89 eyes of 72 patients that were injected with 4 mg/0,1 ml of IVTA for treatment of macular edema was performed. Observation period ranged from 3 to 30 months (mean observation period 12,02 ± 0,94 months).SOH was evaluated in 32 patients (39 eyes, 43.8 ± 5,26%). The mean level of IOP elevation was 10.9 ± 1,00 mmHg (5 - 27.3 mmHg). In 9 % cases high «steroid response» was revealed. However, in 9% of cases there is a pronounced "steroid response". 5 eyes (5,6%) with diabetic macular edema showed persistent ocular hypertension despite full glaucoma medications and required filtering surgery to control IOP. We have not found any reliable correlations between baseline IOP/related systemic diseases and IOP elevation after IVTA. İt is essential to be careful in recommendation of repeat İVTA injection to patients demonstrated SOH after first IVTA injection.